Modification of Asphalt Modified by Packaging Waste EVA and Graphene Oxide - Zhang, Maorong; Lian, Chao; Wang, Junyuan; Wang, Hongfu; Cheng, Bo (Frontiers in Materials, 2022)
A composite modifier made from waste ethylene-vinyl acetate copolymer (WEVA) and graphene oxide (GO) is used to modify the asphalt adopted to pave the roadway. At the same time, the effect of GO on the related properties of the composite modified asphalt is investigated in terms of softening point, penetration, ductility as well as distribution. The preparation of the composite modifier can reduce the modification's complexity and enhance the modifier's dispersity in the asphalt system in the storage phase. By increasing WEVA and GO contents, the softening point of the modified composite asphalt raises, and both the penetration and ductility decrease. It proved that the high-temperature performance of the composite asphalt modified by WEVA and GO is better than that of modified asphalt with WEVA. The distribution characteristics of modified asphalt on a Fluorescence microscope shows that by adding more GO, we get more even and smaller "bee structures" asphalt system. It indicates that GO can promote dispersion and stop the aggregation of WEVA. FTIR spectrum results show that the composite modification by adding WEVA and GO is a physical modification, indicating GO can physically prevent the aggregation of the polymers in the storage phase. We present a schematic of the effect on GO and WEVA in asphalt modification to show the improvement of the distribution of the asphalt system from GO. In all, this study provides an idea for the preparation of modified composite asphalt and the application of nano-materials.